Fatores relacionados à adesão das drogarias e farmácias de Tatuí-SP no projeto Farmácias Notificadoras - Barreto, Gabriela Gueri; Simões, M. J. S. [UNESP] (My University, 2008)
Pharmacovigilance is accomplished by voluntary notification of suspected adverse reactions, medication errors, and deviations from quality, by users and health professionals, through the filling in of forms that are sent to a data bank. To broaden the sources of notifications, the National Health Surveillance Agency (ANVISA), in partnership with the Regional Pharmacy Council (CRF) and Center for Health Surveillance (CVS) of each state, introduced the scheme of Notifying Pharmacies. The present study was aimed at determining the factors influencing the decision of drugstores and private pharmacies in Tatuí/SP in 2007, to join this project A descriptive, observational survey of knowledge, attitude and practice (KAP) was applied to volunteer pharmacists in the town. The results showed that the professionals are awave of pharmacovigilance, (95.24%) and have attitude (95.24%). However, practice is limited (6.0%). Based on this information we concluded that the low support of the project was due to lack of time, interest and no information about the benefits to society of such activity and a lack of support from the pharmacists' organizations. This situation is expected to change with the current introduction of a professional profile, the fusion of professional bodies and the promotion of social awareness on pharmacovigilance.

A farmacovigilância é realizada através de notificações voluntárias de suspeitas de reações adversas, de erros de medicações e de desvios de qualidade, por usuários e profissionais da saúde, através do preenchimento de formulários enviados a um banco de informações. Para ampliar as fontes de notificações, a Agência Nacional de Vigilância Sanitária (ANVISA), em parceria com o Conselho Regional de Farmácia (CRF) e Centro de Vigilância Sanitária (CVS) de cada Estado, introduziu o projeto das “Farmácias Notificadoras”. O presente estudo teve o objetivo de determinar os fatores envolvidos à adesão das drogarias e farmácias privadas de Tatuí/SP, em 2007, no projeto farmácias notificadoras. Realizou-se um estudo observacional descritivo, do tipo inquérito de Conhecimento, Atitude e Prática (CAP) aplicado aos 21 farmacêuticos voluntários da pesquisa. Os resultados revelaram que os profissionais possuem conhecimento de farmacovigilância (95,24%) e atitude (95,24%), entretanto, a prática é limitada (6,0%). Baseado nas informações concluiu-se que a baixa adesão ao projeto ocorre por falta de tempo, desinteresse, falta de informação à sociedade sobre os benefícios dessa atividade e falta de apoio das entidades de classe. Espera-se mudar essa realidade com a atual introdução do perfil profissional generalista, a união das entidades de classe e a promoção da conscientização social sobre farmacovigilância. Palavras-chave: farmacovigilância; reações adversas; atenção farmacêutica; farmácias notificadoras; farmácia.
Factors affecting the accession of private drugstores and pharmacies in Tatuí city (state of São Paulo) into the Notifying Pharmacy Scheme
Keywords: Adverse reactions; Notifying pharmacies; Pharmaceutical attention; Pharmacies; Pharmacovigilance; attitude to health; Brazil; drug surveillance program; factorial analysis; health care access; health care organization; health service; observational study; pharmacist; pharmacist attitude; pharmacy; professional knowledge